The role of invariant natural killer T cells and lipids in the development of allergic sensitisation - Hopkins, Georgina (2023)
Introduction IgE-mediated food allergies are increasing in prevalence, currently affecting 2.6% of infants in the UK. However, the mechanisms underpinning the first phase of IgE-mediated allergy, allergic sensitisation, are still not clear. Recently, the potential involvement of lipids in allergic sensitisation has been proposed, with reports that they can activate invariant natural killer T (iNKT) cells, to secrete Th1 and Th2 cytokines. However, the existing research in this area is limited and predominantly use murine models. Thus, this research developed a human in vitro method to study the role of lipids and iNKT cells in a model of allergic sensitisation. This method was applied to peanut allergy, one of the most common food allergies in children and adults. Thus, the total lipid fraction from peanuts (peanut oil) was utilised with and without the lipophilic peanut allergen, Ara h 8, to examine any influence on iNKT cell cytokine production, comparing between peanut-allergic and non-allergic individuals.